Growth Analysis Of Mudharabah Musyarakah Mu-Rabahah At Bank Mandiri Syariah - Dokman Marulitua Situmorang; Tries Handriman Jamain; Eni Duwita Sigalingging; Muhammad Yusuf (Jurnal Proaksi, 2023)
The condition of sharia banking before Covid-19 was very good and this was the government's aim to merge so that government sharia banks would be stronger and able to develop. The aim of this research is to see the growth of Mudharabah Musyarakah Murabahah at Bank Mandiri Syariah before the merger and the initial conditions of the COVID-19 pandemic. This research is included in qualitative research using a descriptive approach. In this case, the researcher obtained secondary data from Bank Mandiri Syariah's financial reports from 2011 to 2020. The results of the research were that Bank Mandiri Syariah's Mudharabah Transactions experienced a decline from 2011 to 2020, this was due to low mudharabah financing and financing of mudharabah proceeds. increasingly inefficient. Meanwhile, Bank Mandiri Syariah's Musyarakah Transactions increased from 2011 to 2020, this happened because of the large number of customers borrowing and the start of the Covid-19 pandemic in early 2020. Then Bank Mandiri Syariah's Murabahah Transactions also increased.